Studi Efektifitas Lampu Perangkap Hama Padi Tenaga Surya dalam Konteks Ekologi Pertanian - Khen Dedes; Fatimatuzzahra Fatimatuzzahra; David Juli; Akas Bagus Setiawan; Mujiono Mujiono (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2025)
The increasing intensity of pest attacks on rice plants is one of the major factors contributing to the decline in productivity and quality of yields in Indonesia’s agricultural sector. Farmers’ excessive dependence on chemical pesticides not only leads to pest resistance but also poses negative impacts on human health, the environment, and the ecological balance of paddy fields. Therefore, there is an urgent need for innovative, environmentally friendly, efficient, and sustainable pest control technologies. This study proposes the implementation of a solar-powered pest trap lamp integrated with an Internet of Things (IoT)-based system as an alternative solution within an integrated pest management (IPM) framework. The device is designed to utilize solar energy as its primary power source to support energy-efficient operations while reducing dependence on conventional electricity. The IoT connectivity enables real-time data transmission to a cloud-based server for remote monitoring, data analysis, and evidence-based decision-making. Through this approach, pest control can be carried out more precisely, efficiently, and adaptively according to field conditions. Moreover, the application of this technology has the potential to minimize the use of chemical pesticides, enhance agroecosystem health, and promote the principles of sustainable agriculture and national food security. This study emphasizes that the integration of solar energy and IoT technology in pest trap systems can serve as a significant innovation in the digital modernization of agriculture in Indonesia. Further research recommendations include large-scale field trials, quantitative analysis of pest population reduction effectiveness, and evaluation of the economic, social, and adoption aspects among farmers. Hence, this study is expected to provide a substantial contribution to the development of intelligent, efficient, and sustainable pest management systems.